Social preferences and cognitive reflection: evidence from a dictator game experiment - Ponti, Giovanni; Rodriguez-Lara, Ismael (Frontiers in Behavioral Neuroscience, 2015)
This paper provides experimental evidence on the relationship between social preferences and cognitive abilities, which we measure using the Cognitive Reflection Test (CRT). We elicit social preferences by way of 24 dictatorial situations, in which the Dictator’s choice sets include i) standard Dictator games, where increasing the Dictator’s payoff yields a loss for the Recipient, ii) efficient Dicator games, where increasing the Dictator’s payoff also increases that the Recipient’s; as well as other situations in which iii) either the Dictator’s or iv) the Recipient’s monetary payoff is held constant. We partition our subject pool in three groups: reflective (scoring 2 or more in the CRT), impulsive (opting twice or more for the “intuitive” but wrong answers in the CRT) and the remainder. We find that impulsive Dictators show a marked inequity aversion attitude, especially in standard Dictator Games. By contrast, reflective Dictators show lower distributional concerns, except for the situations in which the Dictators’ payoff is held constant. In this case, reflective Dictators give significantly more.